The Relationship between Parents' Understanding and Expectations with Project-Based Learning Reviewed from Age and Educational Status: Hubungan Pemahaman dan Harapan Orang Tua dengan Pembelajaran Berbasis Proyek Ditinjau dari Usia dan Status Pendidikan - Indrawati, Elly; Raharjo, Tri Joko; Formen, Ali (Pendidikan Guru PAUD Universitas PGRI Semarang, 2025)
Abstract Parent’s profile is important in early childhood development. The purposes this research were to analyze acorrelation 1) parents’ understanding with PjBL; 2) parents’ understanding with PjBL in view of parents’ age 3) parents’ expectation with PjBL; 4) parents’ expectation with PjBL in view of parents’ age; 5) parents’ understanding and expectation with PjBL; 6) parents’ understanding and expectation with PjBL in view of parents’ education status. Quantitative method used in this research.The results of this research: 1) There is a correlation between parents’ understanding with project based learning with value 0,531; 2) There is a correlation between parents’ understanding with project based learning in view of parents’ age with value 0,532; 3) There is a correlation between parents’ expectation with PjBL with value 0,513; 4) There is a correlation between parents’ expectation with project based learning in view of parents’ age with value 0,510; 5) There is a correlation between parents’ understanding and expectation with PjBL with value 0,668; 6) There is a correlation between parents’ understanding and expectation with PjBL in view of parents’ education status with value 0,794. The conclusion of this research was profile influenced project based learning in kindergarten. Abstrak Profil orang tua penting dalam perkembangan anak usia dini. Tujuan penelitian ini adalah untuk menganalisis hubungan 1) pemahaman dengan PjBL; 2) pemahaman dengan PjBL ditinjau dari usia orang tua; 3) harapan orang tuadengan PjBL; 4) harapan orang tua dengan PjBL ditinjau dari usia orang tua; 5) pemahaman dan harapan orang tua dengan PjBL; 6) pemahaman dan harapan orang PjBL ditinjau dari status pendidikan orang tua. Metode kuantitatif digunakan dalam penelitian ini.asil penelitian ini antara lain:1) ) Terdapat hubungan antara pemahaman dengan pembelajaran berbasis proyek dengan nilai 0,531; 2) Terdapat hubungan antara pemahaman dengan pembelajaran berbasis proyek ditinjau dari usia orang tua dengan nilai 0,532; 3) Terdapat hubungan antara harapan orang tua dengan pembelajaran berbasis proyek dengan nilai 0,513; 4) Terdapat hubungan antara harapan orang tua terhadap pembelajaran berbasis proyek ditinjau dari usia orang tua dengan nilai 0,510; 5) Terdapat hubungan antara pemahaman dan harapan orang tua terhadap pembelajaran berbasis proyek dengan nilai 0,668; 6) Terdapat hubungan antara pemahaman dan harapan orang tua terhadap pembelajaran berbasis proyek ditinjau dari status pendidikan orang tua dengan nilai 0,794. Kesimpulan dari penelitian ini adalah profil orang tua mempengaruhi pemahaman dan harapan orang tua terhadap pembelajaran berbasis proyek di TK. Kata kunci: Orang Tua; Pemahaman; Harapan; Pembelajaran Berbasis Proyek (PjBL)